The Role Of Correctional Institutions In Ensuring The Right To Health Of Prisoners In Indonesia: A Systematic Literature Review - Efendi, Ervan; Hariansah, Syafri (Dinasti Research, 2024)
Prison inmates have the right to receive the same health services as Indonesian citizens, and must be served well and without discrimination. Fulfillment of these rights must be in accordance with human rights in Indonesia. The role of correctional institutions in carrying out the coaching function is stated in Law Number 22 of 2022 concerning correctional institutions. This research aims to examine literature reviews related to the role of correctional institutions in ensuring the right to health of prisoners. The research method uses the SLR (Systematic Literature Review) method. Data collection was obtained by documenting articles related to similar research. The articles obtained and used in this research were 8 national journal articles that could be obtained from the Google Scholar database using the publish or perish application. Based on the research results, the role of correctional institutions has been to implement prisoners' health rights, but this has not been carried out optimally and optimally due to several obstacles in the process of training prisoners.